2021
DOI: 10.1097/iop.0000000000001813
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use After Orbital, Eyelid, or Lacrimal Surgery

Abstract: Purpose: Opioids may be indicated to mitigate pain after oculofacial surgery. The opioid crisis prompted attention to how these medications are dispensed and disposed. This study aims to characterize opioid usage and handling of patients undergoing oculofacial plastic surgery. Methods: Eighty-nine adult patients were surveyed on their opioid usage after undergoing orbital, lacrimal, or eyelid (including esthetic) surgery at a tertiary oculofacial plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, a 2019 survey study among members of the American Society of Ophthalmic Plastic and Reconstructive Surgery showed that postoperative opioids for oculoplastic and orbital procedures were prescribed at a higher rate than for procedures of other ophthalmic subspecialties and than the national mean. Further, recent studies on opioid use in oculoplastic and orbital surgery demonstrated that prescriptions frequently exceeded patients’ needs . In this study, we aimed to perform an in-depth examination of opioid prescribing patterns for oculoplastic and orbital procedures and identify changes in prescribing patterns before and after enactment of statewide opioid legislation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a 2019 survey study among members of the American Society of Ophthalmic Plastic and Reconstructive Surgery showed that postoperative opioids for oculoplastic and orbital procedures were prescribed at a higher rate than for procedures of other ophthalmic subspecialties and than the national mean. Further, recent studies on opioid use in oculoplastic and orbital surgery demonstrated that prescriptions frequently exceeded patients’ needs . In this study, we aimed to perform an in-depth examination of opioid prescribing patterns for oculoplastic and orbital procedures and identify changes in prescribing patterns before and after enactment of statewide opioid legislation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent studies on opioid use in oculoplastic and orbital surgery demonstrated that prescriptions frequently exceeded patients' needs. 12,13 In this study, we aimed to perform an in-depth examination of opioid prescribing patterns for oculoplastic and orbital procedures and identify changes in prescribing patterns before and after enactment of statewide opioid legislation.…”
mentioning
confidence: 99%